Demographic Change and Economic Growth Simulations on Growth Models - Weber, Lars.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2010)
In this book the author investigates the impact of demographic change on economic growth. As a result of the current financial crisis, a new view on economics has been demanded by various scientists. The author provides such a new view on economic growth, using a methodology of system dynamics. By applying this method, the author focuses on characteristics of complex systems and analyzes aging and shrinking processes, and not only positive growth. Delays and feedback processes are also considered. This leads to deeper and revealing insights into economic behavior. In doing so, a new semi-endogenous growth model is developed by introducing a specific and detailed population sector (demographic growth model). The book shows and analyzes the behavior of such a model and tests several policy scenarios in a transfer chapter to apply the new theoretical approach on real world problems. The major results are summarized in 15 principles of demographic growth.
Demographic Determinants and Economic Impact -- Neoclassical Growth Theories -- Demographic Growth Model -- Scenario and Policy Analysis -- Conclusion and Outlook.
Keywords: Economics; Computer simulation; Endogenous growth (Economics).; Population; Demography; Economics/Management Science; Population Economics; Economic Growth; Demography; Simulation and Modeling